Premarital Sexual Behavior among Papua Women: a Qualitative Research - Yosefina Marijke Watofa; Suryanto Suryanto; Hari Basuki (Universitas Ahmad Dahlan, 2019)
Abstract Sexual behavior outside of marriage means practicing sexual relations outside of marriage. This activity can cause problems like health and psychology of sexually transmitted infections, unwanted pregnancies, shyness, maternal mortality and HIV/ AIDS. This qualitative research was conducted in the city of Jayapura in November 2017, with the aim to know the attitude of women of Papua against premarital sexual behavior. Observations and interviews were conducted on seven unmarried Papuan women. Participants are in reproductive age (ie between 20 to 23 years). As expected, from the interview the three individuals did not accept this behavior. They say that this behavior is bad for the culture, morality, and value of society in general, especially for young women. Although premarital sexual behavior among Papuan women seems to be an unusual thing, they have knowledge about sexuality and the attitude of rejecting premarital sex. According to them talking about sexual problems in society was still a taboo. Strict cultural controls are a barrier to achieving sexual knowledge. Family factors, religiosity and value systems individual expected as an important factor in preventing premarital sexual behavior, especially among young women. Practical education, the development of individual value systems and the development of positive self-esteem should be given meaningfully to them to avoid and be protected from premarital sexual behavior. The priority of these activities should be given to youth, especially women of productive age. Keywords: Outside marriage, positive self esteem, individual value system, Papuan women